Novel DNA Aptamers that Bind to Mutant Huntingtin and Modify Its Activity - Baehyun Shin; Roy Jung; Hyejin Oh; Gwen E. Owens; Hyeongseok Lee; Seung Kwak; Ramee Lee; Susan L. Cotman; Jong-Min Lee; Marcy E. MacDonald; Ji-Joon Song; Ravi Vijayvargia; et al. (Elsevier, 2018)
The CAG repeat expansion that elongates the polyglutamine tract in huntingtin is the root genetic cause of Huntington's disease (HD), a debilitating neurodegenerative disorder. This seemingly slight change to the primary amino acid sequence alters the physical structure of the mutant protein and alters its activity. We have identified a set of G-quadruplex-forming DNA aptamers (MS1, MS2, MS3, MS4) that bind mutant huntingtin proximal to lysines K2932/K2934 in the C-terminal CTD-II domain. Aptamer binding to mutant huntingtin abrogated the enhanced polycomb repressive complex 2 (PRC2) stimulatory activity conferred by the expanded polyglutamine tract. In HD, but not normal, neuronal progenitor cells (NPCs), MS3 aptamer co-localized with endogenous mutant huntingtin and was associated with significantly decreased PRC2 activity. Furthermore, MS3 transfection protected HD NPCs against starvation-dependent stress with increased ATP. Therefore, DNA aptamers can preferentially target mutant huntingtin and modulate a gain of function endowed by the elongated polyglutamine segment. These mutant huntingtin binding aptamers provide novel molecular tools for delineating the effects of the HD mutation and encourage mutant huntingtin structure-based approaches to therapeutic development.